2021
DOI: 10.3390/pr9091674
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Control of Corticotropin Permeation from Hydrogels across a Natural Membrane in the Presence of Albumin

Abstract: (1) Background: Skin is a difficult barrier to overcome, especially for molecules with masses greater than 500 Da. It has been suggested that albumin may contribute to more effective penetration of many therapeutic substances. In this study, an attempt was made to use albumin in semi-solid formulations to increase the skin penetration of another peptide—corticotropin (ACTH). (2) Methods: Hydrogels were prepared at two concentrations: 15 mg/g and 20 mg/g corticotropin, then albumin was added to them in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…The degree of ACTH penetration was approximately 2.7 times higher (40.76 ± 3.51%). ALB also increased the rate of ACTH permeation by approximately 1.4-fold (p < 0.05) [12].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…The degree of ACTH penetration was approximately 2.7 times higher (40.76 ± 3.51%). ALB also increased the rate of ACTH permeation by approximately 1.4-fold (p < 0.05) [12].…”
Section: Discussionmentioning
confidence: 88%
“…ALB caused a delay in penetration that was dependent on the ratio of ALB to ACTH. Apparently, this effect was seen at a 1:1 ratio of ALB and ACTH (1.5% ALB and 1.5% ACTH) [12].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Thus, researchers from University of Pittsburgh constructed a hydrogel sensor using HSA, and it can be used to monitor protein-ionic species binding ( Cai et al, 2014 ). Xu et al constructed a HSA-based hydrogel which reduces random flap necrosis by attenuating the apoptotic and inflammatory effects of vascular endothelial cells, and its effectiveness has been well proven at the cellular and animal level ( Siemiradzka et al, 2021 ). In 2021, Xu et al constructed a composite hydrogel based on HSA, which can be used for gastric pH monitoring in situ magnetic resonance imaging (MRI) ( Xu et al, 2021 ).…”
Section: Hydrogels Based On Different Types Of Albuminmentioning
confidence: 99%
“…Another study [40] investigated the effect of albumin (Alb) added to glycerol hydrogel on the permeation of corticotropin (ACTH). It was found that, depending on the amount of albumin used, it can delay or increase the hormone release process.…”
Section: Permeation Enhancement Technologiesmentioning
confidence: 99%